PENYATUAN KALENDER ISLAM - Taufiqurrahman Kurniawan (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2014)
This study discusses the question of determining the Islamic calendar that has become dilemma among Muslims and causes endless disputes. In response to this, the practitioners of astronomy attempt to unify the dispute by trying to make the world dating guidelines. This step is one of Muslims’ efforts to respond the never ending disagreement. So the author felt it is important to examine the International Islamic calendar as a concrete step in achieving similarity and equality of International Islamic calendar.In this study, the author uses library research by using secondary and descriptive data. Data analysis technique is historical normative qualitative analysis. This has the reason that the observation of astronomical theories, especially the Islamic calendar needs to be observed through history since classical Islamic era until modern Islamic era, the era of classical Islam is observed through texts while modern Islamic era is observed by experiment so it can be found astronomically accurate research results.Keywords: Islamic calendar, classical Islam, modern Islam.